2009
DOI: 10.1103/physrevd.79.034026
|View full text |Cite
|
Sign up to set email alerts
|

Z+(4430)and analogous heavy flavor states

Abstract: The proximity of Z + (4430) to the D * D 1 threshold suggests that it may be a D * D 1 molecular state. The D * D 1 system has been studied dynamically from quark model, and state mixing effect is taken into account by solving the multichannel Schrödinger equation numerically. We suggest the most favorable quantum number is J P = 0 − , if future experiments confirm Z + (4430) as a loosely bound molecule state. More precise measurements of Z + (4430) mass and width, partial wave analysis are helpful to understa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(118 citation statements)
references
References 87 publications
(112 reference statements)
5
113
0
Order By: Relevance
“…The interaction between a quark and an antiquark includes the short distance one-gluon exchange potential and the long distance confinement interaction [235]. After solving the multichannel Schrödinger equation, they found that the Z + (4430) can be explained as a looselyD 1 D * molecular state with J P = 0 − [235], which is consistent with the conclusion from the OPE model [203].…”
Section: A Short Summarysupporting
confidence: 74%
See 3 more Smart Citations
“…The interaction between a quark and an antiquark includes the short distance one-gluon exchange potential and the long distance confinement interaction [235]. After solving the multichannel Schrödinger equation, they found that the Z + (4430) can be explained as a looselyD 1 D * molecular state with J P = 0 − [235], which is consistent with the conclusion from the OPE model [203].…”
Section: A Short Summarysupporting
confidence: 74%
“…The authors concluded that the interaction of D * andD 1 is attractive in the J P = 0 − channel but not strong enough to form a bound state [508,509]. Both the phenomenological models [202,203,235,233] and the quenched lattice QCD calculations [508,509] indicated that the S-wave D 1D * interaction is attractive. The authors of Ref.…”
Section: A Short Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by the nucleon-nucleon interactions, we further extended the one pion exchange model to include the short distance contributions from the heavier bosons η, σ, ρ and ω exchanges in Ref. [22]. We have also taken into account the contribution of the "δ function" term, which leads to a δ function term in the effective potential in configuration space when no regularization is used.…”
Section: Introductionmentioning
confidence: 99%